Factors influencing nurses’ readiness in natural disaster emergency response - Fibriyanti, Efi; Madyaningrum, Ema; Alim, Syahirul (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The response phase is crucial in a disaster, nurses at community health center play a strategic role in disaster response phase preparedness; however, the factors that influence the level of nurse preparedness in the disaster response phase have not been widely studied. Purpose: To identify factors contributing to nurse preparedness during the disaster response phase. Method: A quantitative multicenter study using a cross-sectional design was conducted involving nurses from 27 primary healthcare centers located in disaster-prone regions. Convenience sampling was used to recruit 225 nurses, with data collection taking place between February and March 2023. Instruments included a demographic questionnaire and the Emergency Preparedness Information Questionnaire (EPIQ). Data were analyzed using multivariate logistic regression. Results: A total of 50.9% of nurses had low preparedness. Factors associated with preparedness in the response phase include education level (p=0.002), years of service (p=0.049), training (p=0.001), and disaster experience of serving in disaster (p=0.001). The logistic regression analysis identified the dominant factors in increasing preparedness, which include disaster training (20.6%), professional education level (5.16%), 11-20 years of service (1.39%), male gender (1.34%), and experience of serving in disaster (1.16%). Nurses who have received disaster training have higher preparedness compared to those with BTCLS and BLS training. This predictor is identified to improve response phase preparedness. Nurses can be given disaster training to improve preparedness. Conclusion: The average level of nurse preparedness was categorized as low. The most dominant factor influencing nurse preparedness in the natural disaster response phase was disaster training.